Saving the public from the private? Incentives and outcomes in dual practice - Michael Kuhn; Robert Nuscheler (Vienna University of Technology, Institute of Mathematical Methods in Economics, Research Group Economics, 2013)
We consider a setting of dual practice, where a physician offers free public treatment and, if allowed, a private treatment for which patients have to pay out of pocket. Private treatment is superior in terms of health outcomes but more costly and time intensive. For the latter reason it generates waiting costs. As patients differ in their propensity to benefit from private treatment and in their costs of waiting for treatment, we study the physician's incentives to supply private care and to allocate waiting time to public and private sectors and contrast it with the first-best allocation. The physician shifts waiting costs to public patients in order to increase the willingness-topay for private treatment. While this waiting time allocation turns out to be socially optimal, the resulting positive network effect leads to an over-provision of private care if and only if waiting costs are sufficiently high. A second-best allocation arises when the health authority selects physician reimbursement in the public segment but has no control over private provision. Depending on the welfare weight the health authority attaches to physician profits a ban of dual practice may improve on the second-best allocation. Due to patient heterogeneity, such a ban would affect patients differently.
Keywords: I11; I18; H51; L33; L51; 330; dual practice; health outcomes; health care financing; provider contract; waiting times